A COMPUTER EXPERIMENT TO STUDY THE CHARGINGPROCESS FOR DUST GRAINS IN THE PLASMA - Abdulla, Rahman; Khalaf, Thamir; Shahad, Shaima'a (Iraqi Journal of Science, 2024)
Dust grain in plasma is charged up by collecting electrons and ions from theplasma, this charging process has been studied for laboratory dusty plasma. TheOrbital Motion Limited theory predicts the electron and ion currents toward thegrain, the discrete charging model uses these current values and converts it toprobabilities for collecting individual electrons and ions, this model assumed thatdiscrete charges will be collected at random intervals in a random sequence.A program with FORTRAN programming language has been built to translate thediscrete model to simulate the charging process. Then, the value of the chargenumber and their fluctuations as a function of time, charging time and meanequilibrium charge number on the grain surface have been predicted. It has beenconcluded that the grains were charged with negative and the charging process, ingeneral, was affected by grain size, electron temperature, and the backgroundplasma type.